Mutaba'ah Program in the Development of Tahfidz Al-Qur'an in Private Smp Al-Fath Singkuang District Muara Batang Gadis Mandailing Natal Regency - Harahap, Nur Ikhwana; Sinaga, Ali Imran; Haidir (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
Many problems faced by memorizers of the Qur'an such as not being able to memorize correctly according to makhraj and tajweed, there are still many students who have not memorized perfectly, lack of dividing time in repeating, not focusing on memorizing, that is why it is not easy to memorize the Qur'an. This research is a qualitative research. The object of this research is the Principal, Head of Tahfiz Coordinator, Tahfiz teachers and students of Al-Fath Private Junior High School, especially class VII. The data collection techniques used are interviews, observation and documentation. The stages taken are data reduction, data presentation and conclusion drawing. The results of this study indicate that: (1) Mutaba'ah program in fostering tahfidz Al-Qur'an has been running well (2) The implementation of tahfiz is carried out every Monday-Friday. Before students add new memorization, the ustad or ustadzah mentallyqinkan (read) the verse first, after which students follow together. For students who have memorized directly deposit their memorization one by one. (3) Evaluation is carried out into several stages in 1 year The exam is carried out for 3 days, namely Monday, Tuesday and Wednesday. (4) Supporting factors in the implementation of this program are age, teacher criteria, motivation from parents and teachers, facilities and infrastructure. While the inhibiting factors in the implementation of the tahfiz program are students, lack of time management, and forgetfulness.